Committee on International Accounting. (The Accounting Review, 1973)
The article presents a report of the Committee on International Accounting of the American Accounting Association on the financial control and reporting problems of the companies amid the increase in foreign operations of the companies as of October 1973. The teaching approach should in most instances be directed to topics relating to conducting operations across national boundaries as well as to comparative accounting. Ultimately the entire accounting curriculum should be internationalized, a great many domestic accounting problems have international counterparts and these international dimensions should in many cases be integrated into the existing accounting courses that examine the domestic problems. With respect to taxable bases, the concept of income and revenues, the determination of what expenses are to be matched against revenues and when, and the sources of taxable income are variables which differ among nations. Evaluation of the impact of tax considerations on international operating and investment decisions and on operating procedures is required.